The ulū al-albāb approach of life-long philanthropy among knowledge workers - Mhd. Sarif, Suhaimi (UiTM Press, 2018)
This paper postulates the Ulū al-Albāb approach in creating, nurturing, and building conducive environment for philanthropy spirit among knowledge workers in Malaysia. The Ulū al-Albāb approach is spiritual-based knowledge management that offers an integrative framework to achieve sustainable knowledge management and organizational learning. The existing working environment in technology-based firms lacks of spirituality foundation to sustain the motivation for philanthropy spirit among knowledge workers in technology-based firms. This study interviewed knowledge workers to solicit their views on how the Ulū al-Albāb approach in creating, nurturing, and building conducive environment for philanthropy spirit among knowledge workers in technology-based. The feedback from the informants argued that the philanthropy spirit has been in line with knowledge workers’ own thinking, attitude and action without realizing that they have been making endowment, charity and giving in material, kind, and contribution of Ulū al-Albāb contents. The current stage of the Ulū al-Albāb approach has to be operationalized to fit into the contemporary business models and processes. However, the views of the knowledge workers are not comprehensive and rigorous without the views from other stakeholders. Nevertheless, managers can apply the Ulū al-Albāb approach into its communities of practice and social network. The Ulū al-Albāb approach contributes to the theoretical and practical understanding of knowledge management development.